PENINGKATAN PENGETAHUAN TENTANG PENTINGNYA UPDATING DATA SINTA MELALUI EDUKASI ONLINE DI LINGKUNGAN UNIVERSITAS - Baharudin, Erwan; Ernawati, Ernawati; Arianto, Henry; Cahyadi, Lukman; Ramadhan, Yanuar (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
The spread of the COVID-19 is the cause of death with the highest number in the world so that the government enforce work from home rule.The work from home rule causes activities such as teaching and learning, training, and seminar conducted via online education. The purpose of this activity is to educate online about the importance of updating data in sinta. The method of activity is carried out with socialization (lecture) and FGD (Focus Group Discussion). The target of this activity is the campus community consisting of staff-bureaus, lecturers, and the rest of the university staff. The number of participants who participated was 79 people. Most were from the faculty of health sciences (25.3%), law (15.2%), economics and business (13.9%), psychology and engineering (11.4%). The results of the socialization showed that most participants understood about the importance of updating data in sinta; knowledge (good) 51.9%. The results of the FGD showed that participants mainly discussed the creating a sinta account (25%), synchronizing data from old institution to new institution (25%), consulting services in sinta (37.5%), and classifying expertise or research themes in sinta (12.5%). As many as 100% expressed an understanding about updating data in sinta. This activity increased knowledge about the importance updating data in sinta by 48.1%. Thus, it is important to carry out an educational activities especially with online methods routinely and periodically in an effort to increase knowledge regarding the conditions of the pandemic. Ã‚Â Keywords: Online Education, COVID-19, Knowledge, Sinta